ACTR-27. EVOLUTION OF THE NEUROSURGEON'S ROLE IN CLINICAL TRIALS FOR GBM: A SYSTEMATIC OVERVIEW OF THE CLINICALTRIALS.GOV DATABASE. (11th November 2019) - Mansouri, Alireza; Beyn, Michelle; Pancholi, Aditya; Chow, Clement; Boutet, Alexandre; Elias, Gavin; Germann, Jurgen; Zadeh, Gelareh
Abstract: BACKGROUND: The therapeutic challenge of glioblastoma (GBM) has catalyzed the active pursuit of a high volume of clinical trials to evaluate novel interventions for this deadly disease. Our enhanced understanding of the biology of GBMs has translated into an evolution of the role of the neurosurgeon as well. In this study, we have evaluated the current landscape of surgical clinical trials in GBM to characterize this evolution, describe current trends, and identify potential gaps in methodological features. METHODS: The ClinicalTrials.gov database was searched for surgical/procedural trials in individuals with GBM on May 14 th, 2019 without date limitations. Demographics, specific intervention (e.g. technical, device use, or local drug delivery), phase, sample size, and main outcome measures were abstracted. RESULTS: 270 of 2140 trials (12.6%) were identified as procedural. The majority were based in the USA (189/270, 70%), single-center (188/270, 70%), and not randomized by design (215/270, 80%). Primary and recurrent GBMs were evenly addressed. Industry-funding supported 106/270 (39%) of studies. The leading test intervention was local delivery of therapeutics (44.8%), followed by use of novel devices (33%). Surgical technique/procedures comprised 20%. Early Phase designs predominated (177/270, 65.5%) but 67 (24.8%) did not report Phase. The greatest surge in new registrations over the last decade was seen in Phase I trials. The top primary outcome was safety/tolerability/ feasibility (107/270, 39%), followed by survival (62/270, 22%); 35 (12.6%) did not report a primary outcome. Approximately 15% of studies were terminated, withdrawn or suspended. Only 6 records were associated with reported results. CONCLUSIONS: In GBMs, procedural interventions comprise a notable proportion of trials. Local delivery of therapeutics and novel device applications, predominantly through Phase I designs, represent the evolved role of the neurosurgeon in neuro-oncology. Improved documentation of design, outcomes, and reporting of results are needed to better inform the field and increase efficiency.